2019
DOI: 10.1002/iub.2175
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A aggravates renal ischemia–reperfusion injury by disrupting mitochondrial homeostasis and N‐acetylcysteine mitigates the injurious outcomes

Abstract: Exposure to bisphenol A (BPA), a chemical generally used in consumer products, becomes a global public health concern, as humans are increasingly exposed through their daily consuming activities. Renal ischemia–reperfusion (RIR) is the major cause of acute kidney injury with high prevalence and increased long‐term risks for multiple comorbidities and mortality. As the kidney is susceptible to these conditions, we explored whether the outcomes following the RIR episode could be influenced by BPA exposure, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
(132 reference statements)
0
21
0
Order By: Relevance
“…26 Although, these treatments have failed to reduce the mortality rate of AKI worldwide. 27 Prevention of AKI is currently receiving increased attention.…”
Section: Fg-4592 Ameliorated Dna Damage After Iri-akimentioning
confidence: 99%
“…26 Although, these treatments have failed to reduce the mortality rate of AKI worldwide. 27 Prevention of AKI is currently receiving increased attention.…”
Section: Fg-4592 Ameliorated Dna Damage After Iri-akimentioning
confidence: 99%
“…SIRT3 overexpression was found to confer renal protection via the suppression of superoxide generation [ 84 ]. Reduced expression of SIRT3 was associated with increased severity of I/R-induced kidney injury, while restoration of SIRT3 reversed this damage by modulating mitochondrial homeostasis through the AMPK/PGC-1α pathway [ 85 ]. A recent study reported that SIRT5 was highly expressed in both the mitochondria and peroxisomes of proximal tubular cells, but the opposite trend was observed in I/R-induced kidney injury compared to other types of sirtuins, as the loss of SIRT5 function led to renoprotective effects after I/R injury; shifting of fatty acid oxidation from the mitochondria to the peroxisome under the control of SIRT5 was suggested as the underlying mechanism.…”
Section: The Role Of Sirtuins In Renal Diseasementioning
confidence: 99%
“…Detection of protein was performed using Bio-Rad’s Clarity ECL Western Blot Substrate kits and the blot bands were developed in ChemiDoc Touch Imaging System (Bio-Rad Laboratories, Inc., Philadelphia, PA, USA). Analysis of protein expression was determined by the Image J program [ 21 ]. Each protein expression was normalized with β-actin expression.…”
Section: Methodsmentioning
confidence: 99%